2022
DOI: 10.3390/metabo12060488
|View full text |Cite
|
Sign up to set email alerts
|

The Integration of Metabolomics with Other Omics: Insights into Understanding Prostate Cancer

Abstract: Our understanding of prostate cancer (PCa) has shifted from solely caused by a few genetic aberrations to a combination of complex biochemical dysregulations with the prostate metabolome at its core. The role of metabolomics in analyzing the pathophysiology of PCa is indispensable. However, to fully elucidate real-time complex dysregulation in prostate cells, an integrated approach based on metabolomics and other omics is warranted. Individually, genomics, transcriptomics, and proteomics are robust, but they a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 408 publications
(529 reference statements)
0
7
0
Order By: Relevance
“…The process of analyzing a proteome sample involves separation techniques such as gel electrophoresis for gel-based methods and liquid chromatography (LC) or LC coupled with mass spectrometry (LC-MS) for liquidbased methods [120]. It is worth noting that the cost of implementing proteomics has restricted the number of integrated proteomics-metabolomics studies in the literature, especially when compared to genomics-metabolomics or transcriptomics-metabolomics studies [121]. However, recent developments in proteome mapping and the emergence of top-down proteomics have made this approach more feasible [117].…”
Section: Integrated Metabolomics and Proteomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The process of analyzing a proteome sample involves separation techniques such as gel electrophoresis for gel-based methods and liquid chromatography (LC) or LC coupled with mass spectrometry (LC-MS) for liquidbased methods [120]. It is worth noting that the cost of implementing proteomics has restricted the number of integrated proteomics-metabolomics studies in the literature, especially when compared to genomics-metabolomics or transcriptomics-metabolomics studies [121]. However, recent developments in proteome mapping and the emergence of top-down proteomics have made this approach more feasible [117].…”
Section: Integrated Metabolomics and Proteomicsmentioning
confidence: 99%
“…For instance, distinguishing between PCa and normal prostate cells is achieved through a combination of proteomics and metabolomics, which enables the analysis of dysregulated lipid metabolism and increased protein phosphorylation [122]. The evolution of computing capabilities has allowed this integrated approach to move beyond simple pathway mapping [121]. In the future, through the integration of various metabolomic datasets and advancements in AI methodologies, novel biomarkers for early cancer detection could be discovered [123].…”
Section: Integrated Metabolomics and Proteomicsmentioning
confidence: 99%
“…Unlike other omics, the metabolome is highly sensitive to stimuli and provides a snapshot of the real-time physiological state of the observed system. Additionally, complex mechanisms of information transfer between other omics layers (post-transcription and post-translation) do not always allow omics like transcriptomics and proteomics to correlate with the observed phenotype [92]. With this in mind, we performed an untargeted analysis of the calli metabolome to obtain insight into the principal metabolic mechanisms that drive somatic embryogenesis.…”
Section: One-way Analysis and Metabolite Ratiosmentioning
confidence: 99%
“…In addition, research has indicated the direct involvement of the metabolome in genome regulation [11]. Metabolomics also serves as an input that influences genomic alteration to form a feedback loop [12,13]. There are interactions between metabolites and gene expression [14,15].…”
Section: Introductionmentioning
confidence: 99%